Traditional Knowledge of Mushroom Utilization by the Dayak Kubin Tribe: A Case Study in Nanga Raku Village, West Kalimantan - Yeni, Laili Fitri; Faturrahman, Mas Akhbar; Widyastuti, Desinta Ayu; Syakuran, Luqman Abdan (Universitas Negeri Semarang, 2025)
The Dayak Kubin Tribe, which inhabits Nanga Raku Village, Sayan District, Melawi Regency, West Kalimantan Province, still utilizes mushrooms daily. However, this knowledge has not been documented until now. This research aims to provide information on the diversity of mushroom species and their utilization by the Dayak Kubin Tribe in Nanga Raku Village. This qualitative research was conducted in Nanga Raku Village in May 2022. The informants in this research amounted to 15 people obtained through the snowball sampling technique. The search for mushroom samples was carried out using the cruising method. The results showed that the Dayak Kubin Tribe in Nanga Raku Village utilizes 16 species of mushrooms. Mushroom species used as food sources are Agaricus sp., Auricularia auricula-judae, Auricularia delicata, Termitomyces sp., Lactocollybia sp., Marasmiellus candidus, Pleurotus cystidiosus, Lentinus sajor-caju, Panus sp., Psathyrella sp., Cookeina sulcipes, Cookeina tricholoma, and Schizophyllum commune. Mushroom species utilized as medicines are Microporus affinis and Microporus xanthopus. Hygrocybe sp. is the only mushroom species that is used as a food source and medicinal ingredient at the same time. The ethnomycological information presented in this research is an effort to preserve traditional knowledge by utilizing biodiversity in the surrounding environment.